DESIGN OF DOMESTIC WASTEWATER SEWERAGE SYSTEM IN PALEMBANG CITY SEWERAGE PROJECT ZONE 3 IN ILIR TIMUR 1 AND ILIR TIMUR 3, PALEMBANG CITY - Daffa Hamiid, Muhammad
Palembang City Sewerage Project is a city-scale SPALD-T Development activity in Palembang City which is implemented with multiple funding sources, consisting of Australian Government Grants with a performance-based mechanism where the grant funds are transferred from the Special Account (Reksus) to RKUD as a reimbursement of the use of the Palembang City APBD, APBN, as well as the APBD of South Sumatra Province and Palembang City. This project is a collaborative effort of the Australian Government and the Indonesian Government to improve the sanitation of Palembang City. Given the high groundwater level in Palembang city, local wastewater treatment system is not suitable. Sei Selayur Wastewater Treatment Plant (WWTP) is a WWTP resulting from cooperation between Indonesia and Australia which was inaugurated in 2023. This WWTP is located in Sei Selayur Sub-district, Kalidoni District, Palembang City, with a WWTP area of 5.9 Ha. The current location of the WWTP was chosen because the area previously still had a large amount of vacant land, and the location is near the edge of the Musi River so that the effluent water from the Sei Selayur WWTP can be directly discharged into the water body, namely the Musi River. This WWTP has a processing capacity of 20,300 m3 / day, using processing technologies such as Anaerobic Baffled Reactor (ABR), Biological Trickling Filter (BTF), and Nitrifying Trickling Filter (NTF). However, the construction of the piping network for the distribution of domestic wastewater itself is still in the design stage, so that the operation of the Sei Selayur WWTP has not run optimally. Therefore, a wastewater distribution system design was carried out in the service area to channel domestic wastewater to the Sei Selayur WWTP. The planning of domestic wastewater distribution in Zone 3 of the Palembang City Sewerage Project, Palembang City is carried out in 2 stages, namely problem identification and problem solving. The identification stage includes primary and secondary data collection, while the problem solving stage includes evaluation, analysis, and system design. Path design is done by presenting 3 alternative paths that will be selected through weighting using the Simple Additive Weight (SAW) method. Based on the results of the path calculation, the wastewater generated from Zone 3 PCSP in 2024 is 12019.8 m3/day, and after population projection for the next 20 years (2044) is 18645.9 m3/day. While the service target for wastewater distribution in Zone 3 is 2650.2 m3/day. It can be concluded that the service capacity in 2024 is only 22% and in 2044 only 14.2%.